2017
DOI: 10.1088/1748-9326/aa8f80
|View full text |Cite
|
Sign up to set email alerts
|

Public opinion and environmental policy output: a cross-national analysis of energy policies in Europe

Abstract: This article studies how public opinion is associated with the introduction of renewable energy policies in Europe. While research increasingly seeks to model the link between public opinion and environmental policies, the empirical evidence is largely based on a single case: the US. This limits the generalizability of findings and we argue accordingly for a systematic, quantitative study of how public opinion drives environmental policies in another context. Theoretically, we combine arguments behind the poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(100 citation statements)
references
References 55 publications
(63 reference statements)
0
90
0
Order By: Relevance
“…On a global scale, Weaver (2008) establishes a direct link between support for environmental policies and the ambition level of environmental policies in an analysis of 64 countries. Finally, Anderson et al (2017) find that shifts in public attitudes toward pro-environmentalism lead to increases in renewable energy policies in Europe over the period 1974-2015.…”
Section: Subjective Factors and Climate Policy Ambitionmentioning
confidence: 91%
See 2 more Smart Citations
“…On a global scale, Weaver (2008) establishes a direct link between support for environmental policies and the ambition level of environmental policies in an analysis of 64 countries. Finally, Anderson et al (2017) find that shifts in public attitudes toward pro-environmentalism lead to increases in renewable energy policies in Europe over the period 1974-2015.…”
Section: Subjective Factors and Climate Policy Ambitionmentioning
confidence: 91%
“…Climate policy literature has evaluated the effect of various public opinion variables on the emergence of policies. Much of this research has focused on the United States (Anderson et al 2017). Agnone (2007), for example, finds that pro-environmental attitudes has a positive effect on the enactment of federal environmental legislation in the United States over the period , and that the effect is amplified by protests.…”
Section: Subjective Factors and Climate Policy Ambitionmentioning
confidence: 99%
See 1 more Smart Citation
“…With accurate and timely monitoring of the information, we can find out the public opinion in time at the beginning of the occurrence of public opinion, give positive response, explain and explain, and prevent mistransmission. In the process of expansion of public opinion, in order to focus the content as the center, planning topics, propaganda guidance through the multiple platforms and online interaction, collect understand the opinions of the students thinking, to reflect the problem to be solved quickly feedback to each relevant department and respond quickly released the most authoritative information, promote public opinion with network public opinion monitoring mechanism precision work efficiency [30] [31] [32] [33].…”
Section: Mechanism Construction and Public Opinion Guidancementioning
confidence: 99%
“…For example, one study found that education and experience led to increased understanding of threats facing the region (climate change, human activity), and indeed, over 60% of surveyed tourists supported the implementation of a conservation tax for Antarctic visitors (Vila et al 2016). Policy change is primarily driven through public awareness and pressure (Anderson et al 2017), and an increasing number of visitors, and associated increase in public awareness will only help to fuel this support.…”
Section: Discussionmentioning
confidence: 99%